2017
DOI: 10.1080/2162402x.2017.1321184
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the human T cell repertoire to recurrent driver mutations in MYD88 and EZH2 in lymphoma

Abstract: Oncogenic "driver" mutations are theoretically attractive targets for the immunotherapy of lymphoid cancers, yet the proportion that can be recognized by T cells remains poorly defined. To address this issue without any confounding effects of the patient's immune system, we assessed T cells from 19 healthy donors for recognition of three common driver mutations in lymphoma: , and . Donors collectively expressed the 10 most prevalent HLA class I alleles, including HLA-A*02:01. Peripheral blood T cells were prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…Based on the functional consequence of MYD88 L265P activity, several strategies have been devised to halt its oncogenic activation by targeting IRAK1/4, JAK, and, the most successful target, BTK, or by disrupting the myddosome assembly. Moreover, MYD88 L265P-containing peptides can elicit human leukocyte antigen (HLA) class I-restricted cytotoxic T-cell responses (46,47), supporting the potential for T-cell receptor (TCR)-based immunotherapy (Fig. 1D).…”
Section: Myd88 L265p In Therapeutic Implicationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Based on the functional consequence of MYD88 L265P activity, several strategies have been devised to halt its oncogenic activation by targeting IRAK1/4, JAK, and, the most successful target, BTK, or by disrupting the myddosome assembly. Moreover, MYD88 L265P-containing peptides can elicit human leukocyte antigen (HLA) class I-restricted cytotoxic T-cell responses (46,47), supporting the potential for T-cell receptor (TCR)-based immunotherapy (Fig. 1D).…”
Section: Myd88 L265p In Therapeutic Implicationsmentioning
confidence: 80%
“…Furthermore, P4 B Ã 15 -specific CD8 þ T cells elicited mutant peptide-restricted cytotoxicity (46). In a separate study, Nielsen and colleagues assessed T cells from healthy donors for recognition of MYD88 L265P-containing peptides and identified CD8þ T cells against RPIPIKYKA when presented by HLA-B Ã 07:02 (47). In both cases, healthy individuals harbor T cells with specific TCRs that recognize L265P-containing neoantigens restricted by MHC, highlighting the potential of TCR recognition of MYD88 L265P-derived peptides as a novel personalized therapeutic strategy.…”
Section: Myd88 L265p In Therapeutic Implicationsmentioning
confidence: 99%
“…A previous report showed that both naïve and activated neoantigen-specific T cells could be expanded from the peripheral blood of follicular lymphoma patients by priming with peptide-pulsed DCs ( 77 ). Using the same method, neoantigen-specific T cells were successfully expanded from the peripheral blood of HLA-matched healthy donors ( 30 , 78 ). These preliminary results support the use of naïve T cells as an alternative source for ACT; however, their exceptionally low frequencies in peripheral blood and requirement for repeated stimulation pose hurdles ( 79 ).…”
Section: Isolation Of Neoantigen-specific T Cells From Peripheral Blomentioning
confidence: 99%
“…The correlation of driver mutations with tumor progression may make them better targets for therapeutic immune responses. Neoantigens derived from driver mutations have been identified in lymphoma [41,42], gastrointestinal cancer [43] and melanoma [44]. However, neoantigens are frequently passenger mutations [43,45,46].…”
Section: Properties Of Neoantigensmentioning
confidence: 99%